PENGGUNAAN MEDIA AUDIO DALAM PEMBELAJARAN STENOGRAFI - Martono, S (Fakultas Ekonomi, Universitas Negeri Semarang, 2007)
The objective this study is to know the effectivenes of using audio media in stenografi typing learning. The populationÃÂ of this research was 30 students that divided into two groups; experimental and controlled group consisted of 15 students. Based on the first score in stenografi subject that the two groups have the same abillity but they were given different treatment. For experimental group, they got a treatment of audio media whereas the controlled group didnÃ¢â¬â¢t use audio media. The technique of collecting data were documentation technique and experimental tecnique. The instrument was stenografi speed typing. The final result showed that the using of audio media was more effective and can improve the study result better than controlled group. This result was expected toÃÂ give significance for the stenografi teachers to apply audio media in learning and input for the students that stenografi was not a memorizing subject but it was a skill subject that must be trained by joining the lesson. Thus, people can use stenografi typing to record each talk. Keywords: Learning, Audio Media, Stenografi